Deposition of Thoron Progeny in Human Head Airways - Cheng, Yung-Sung; Su, Yin-Fong; Yeh, Hsu-Chi; Swift, David L. (Aerosol science and technology, 1993)
Radon and thoron progeny are ultrafine particles in the size range of 1-200 nm, depending on whether or not they are attached to other aerosol particles. The diffusion coefficient of radon progeny is a critical parameter in determining its dynamics while airborne. Depending on their diffusion coefficient and the breathing pattern of the subject, ultrafine particles have been shown to deposit in the nasal or oral airways. Substantial deposition in the head airways reduces the amount of radioactivity that deposits in the tracheobronchial tree. Thus, for accurate dosimetric calculations, it is important to know the deposition fraction of radon progeny in the head airways. Several adult head airway models were used to study the radon progeny deposition in human nasal and oral airways. Radon-220 progeny ( 212 Pb) were used in the study. The particle size as measured by a graded screen diffusion battery was between 1.2 and 1.7 nm, indicating that the particles were molecular clusters. Deposition was measured by collecting filter samples before and after the model and gamma counting the 212 Pb. Experiments were performed under the constant flow rates of 4-20 L/min. Deposition efficiences were between 63% and 85% in the nasal airway and 48% and 78% in the oral airway. Previously reported deposition data in the same airway model for ultrafine particles between 4.6 and 200 nm and the deposition data of radon progeny were used to establish a turbulent deposition equation covering particle sizes from 1 to 200 nm, the entire size range for attached and unattached radon progeny.